Evaluating the risk of acute kidney injury and mortality associated with concomitant use of vancomycin with piperacillin/tazobactam or meropenem in critically ill and non-critically ill patients: a systematic review and meta-analysis - Abdulmajeed M. Alshehri; Majed S. Al Yami; Atheer Aldairem; Lama Alfehaid; Abdulaali R. Almutairi; Omar A. Almohammed; Amal Mohammad Badawoud (BMC Infectious Diseases)
Abstract Background There are conflicting findings regarding the risk of acute kidney injury (AKI) and mortality with vancomycin/piperacillin-tazobactam combination (VPT) and vancomycin/meropenem (VM). The aim of this meta-analysis was to compare the risk of AKI and mortality between VPT and VM. Methods Observational studies reporting the incidence of AKI and mortality in patients receiving VPT or VM between January 2017 and September 2024 were retrieved from PubMed, the Cochrane Library, and Web of Science. The primary outcome of the analysis was the risk of AKI, and the secondary outcomes were the mortality rate, need for renal replacement therapy (RRT), and hospital length of stay (LOS). This meta-analysis was conducted using a random-effects model to estimate the odds ratios (OR) and 95% confidence intervals (CI) for AKI, mortality, and RRT or mean difference and 95% CI for the LOS. Results Seventeen studies involving a total of 80,595 patients were included in the analysis. The odds of developing AKI were higher among patients who received the VPT versus those who received the VM combination (OR = 2.02; 95%CI 1.56–2.62). There were no differences between VPT and VM in the mortality and hospital length of stay; however, the odds of requiring RRT were higher among VPT group versus VM group (OR = 1.55; 95%CI 1.23–1.96). Conclusion The findings suggest that the use of VPT is associated with a higher risk of AKI compared to VM and highlight the need for cautious antibiotic selection and monitoring of renal function in patients receiving these combinations.